2015
DOI: 10.1017/s0007114515001634
|View full text |Cite
|
Sign up to set email alerts
|

Associations of diet quality with cognition in children – the Physical Activity and Nutrition in Children Study

Abstract: Evidence on the associations of dietary patterns with cognition in children is limited. Therefore, we investigated the associations of the Baltic Sea Diet Score (BSDS) and the Dietary Approaches to Stop Hypertension (DASH) score with cognition in children. The present cross-sectional study sample included 428 children aged 6 -8 years (216 boys and 212 girls). The BSDS and the DASH score were calculated using data from 4 d food records, higher scores indicating better diet quality. Cognition was assessed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 51 publications
(65 reference statements)
7
59
3
1
Order By: Relevance
“…Studies that met all these criteria and examined food quality or macronutrients are included in Table 1 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) , and studies that examined specific foods are included in Table 2 (17,(27)(28)(29)(30)(31)(32)(33)(34)(35) . Information extracted from each study included the following:…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that met all these criteria and examined food quality or macronutrients are included in Table 1 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) , and studies that examined specific foods are included in Table 2 (17,(27)(28)(29)(30)(31)(32)(33)(34)(35) . Information extracted from each study included the following:…”
Section: Study Selectionmentioning
confidence: 99%
“…This study found that the 'Healthy' dietary pattern was associated with fewer errors on the Groton Maze Learning Test (β = − 0•023; P = 0•035). Haapala et al (17) studied the association between non-verbal fluid intelligence/ abstract reasoning and overall diet quality among 428 children aged 6-8 years in Finland. This study calculated both Dietary Approaches to Stop Hypertension (DASH) scores and Baltic Sea Diet Scores (BSDS) based on 4-d food records and assessed cognitive performance with the Raven's Coloured Progressive Matrixes (CPM).…”
Section: Studies Examining Food Quality or Macronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, compared to their counterparts in the control group, healthy elders who had long-term diet restriction consisting of a 30% reduction in calories experienced improved memory (Witte et al, 2009); similarly, calorie restriction improved the working memory of male mouse lemurs (Dal-Pan et al, 2011). Although studies associated with diet and cognitive function in children are limited, poor diet quality has been linked to lower cognitive performance in the other populations (Haapala et al, 2015). These findings provide initial evidence of the effects of diet restriction on specific cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This is of concern because few youth meet all dietary intake recommendations. 1 Healthier dietary behavior established in childhood has been associated with decreased lifelong risk of many chronic diseases including obesity, diabetes, cardiovascular disease, and some cancers.…”
Section: Introductionmentioning
confidence: 99%